Effect of harvest time on sugar content and carotenoid composition in different sweet maize hybrids - Seyed Mohammad Nasir Mousavi; Arpad Illes; Csaba Bojtor; Younes Miar; Seyed Habib Shojaie; Janos Nagy; Adrienn Szeles (Scientific Reports)
Abstract Sweet maize (Zea mays convar. saccharata var. rugosa) is valued for its high sugar content, which gradually converts to starch during kernel maturation. This study evaluated the yield and biochemical composition of five super sweet maize hybrids (D, M, G, S, and N) across four harvest dates (July 19, July 26, August 2, and August 9) over two consecutive growing seasons. Seventeen key nutritional parameters—including sugars, minerals, and carotenoids—were significantly affected by both hybrid and harvest time (p < 0.05). The M hybrid showed the highest levels of β-carotene (5.61 µg/g), phosphorus (3.45 mg/g), and magnesium (1.96 mg/g), while the S hybrid had the greatest concentrations of lutein (2.84 µg/g), zeaxanthin (2.71 µg/g), and β-cryptoxanthin (1.79 µg/g). The D hybrid recorded the highest sucrose content (78.5 mg/g), and the N hybrid was superior in dry matter (32.7%) and fructose (61.4 mg/g). Harvest timing also had a significant impact: early harvest (July 19) resulted in peak concentrations of β-carotene (5.89 µg/g), potassium (4.17 mg/g), and glucose (84.2 mg/g), whereas late harvest (August 9) favored hybrid-specific nutrient accumulation. Principal Component Analysis (PCA) revealed that the first two components explained 75.82% of the total variance, with glucose and potassium identified as key discriminating traits. These findings highlight the critical role of genotype selection and harvest timing in optimizing the nutritional quality and market value of sweet maize under temperate growing conditions.